Utilization chatbot for Indonesian tourism: a post-pandemic solution of information accessibility - Hesti Fibriasari; Bakti Dwi Waluyo; Baharuddin Baharuddin; Tansa Trisna Astono Putri; Savitri Rahmadany (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Indonesia is a renowned tourist destination worldwide. However, the COVID-19 pandemic has resulted in a decrease in both foreign and domestic tourist visits. Therefore, this research aims to develop a Telegram-based ChatBot application to increase post-pandemic tourist visits. The ChatBot is designed to make it easier for tourists to obtain information related to transportation and accommodation at tourist attractions. The ChatBot is built using the Knuth-Morris-Pratt (KMP) algorithm and web scraping method. The ChatBot's response to the keyword matching is then presented to tourists. To measure travelers' perceptions of ChatBot, the System Usability Scale (SUS) was used. SUS is a questionnaire consisting of 10 questions that were answered by 20 anonymous users. Based on the calculations, the average SUS score is 71, which indicates that the developed ChatBot is in the good category and suitable for use. Using this ChatBot will make it easier for tourists to obtain tourism information in Indonesia. With its ability to retrieve relevant information related to transportation and accommodation at tourist attractions, the ChatBot can serve as a useful tool to increase post-pandemic tourist visits.